2004
DOI: 10.1211/0022357023042
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dialkoxylphenyl compounds with oxime group on macrophage function and the proliferation of lymphocytes

Abstract: Dialkoxyphenyl compounds have been reported to possess anti-inflammatory activity through inhibition of phosphodieseterase (PDE) type IV. In this study, a series of derivatives of dialkoxyphenyl compounds with an oxime group, which is generally known to be one of the biologically active functional groups, were prepared and evaluated for their ability to inhibit the production of inflammatory mediators in activated macrophages and the proliferation of lymphocytes. The structure-activity relationship (SAR) study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…Using ovalbumin-induced allergic asthma model, Kwon et al demonstrated benzofuran derivatives significantly reduced the levels of IL-5, IL-13 and IgE production, eosinophils and macrophages influx, ICAM-1/MCP-1 expression, mucus secretion and airway hyperresponsiveness in mice, suggesting benzofuran exerts protective effect to airway inflammation. Similarly, methoxy-phenyl-oxime derivatives have demonstrated anti-inflammatory activities [28] and dimethyl selenide derivatives alters interleukin-4/13 signalling pathways in vitro [29]. Other previously unreported compounds should be subjected to further investigation into their potential roles in asthma exacerbation and airway inflammation.…”
Section: Summary Of Resultsmentioning
confidence: 99%
“…Using ovalbumin-induced allergic asthma model, Kwon et al demonstrated benzofuran derivatives significantly reduced the levels of IL-5, IL-13 and IgE production, eosinophils and macrophages influx, ICAM-1/MCP-1 expression, mucus secretion and airway hyperresponsiveness in mice, suggesting benzofuran exerts protective effect to airway inflammation. Similarly, methoxy-phenyl-oxime derivatives have demonstrated anti-inflammatory activities [28] and dimethyl selenide derivatives alters interleukin-4/13 signalling pathways in vitro [29]. Other previously unreported compounds should be subjected to further investigation into their potential roles in asthma exacerbation and airway inflammation.…”
Section: Summary Of Resultsmentioning
confidence: 99%
“…Oxime-based phosphodiesterase (PDE) 4 inhibitors are also being evaluated as potential anti-inflammatory agents, as they have the ability to inhibit the production of inflammatory mediators and cytokines [ 185 ]. Several oxime derivatives of rolipram, an inhibitor of PDE4, have been reported to inhibit TNF production in LPS-stimulated RAW264.7 macrophages with higher potency than rolipram [ 186 ]. Interestingly, the E / Z -geometry of oxime was important for activity of these compounds, with cis -isomers being more active than the corresponding trans -isomers [ 186 ].…”
Section: Oximes With Non-kinase Targetsmentioning
confidence: 99%
“…Several oxime derivatives of rolipram, an inhibitor of PDE4, have been reported to inhibit TNF production in LPS-stimulated RAW264.7 macrophages with higher potency than rolipram [ 186 ]. Interestingly, the E / Z -geometry of oxime was important for activity of these compounds, with cis -isomers being more active than the corresponding trans -isomers [ 186 ].…”
Section: Oximes With Non-kinase Targetsmentioning
confidence: 99%
“…Similarly, Cordyceps militaris extract exhibits anti-inflammatory activity by reducing the production and expression of inflammatory mediators in DSS-induced mice with acute colitis [18]. Cordyceps militaris extract is effective in the alleviation of oxidative-stressinduced apoptosis and premature ageing, the inhibition of cancer cell proliferation and the treatment of metabolic disorders caused by obesity [19][20][21]. Although previous research has indicated that cordycepin and Cordyceps militaris extract could modulate the composition of the gut microbiota, the potential mechanisms by which Cordyceps militaris extract and cordycepin regulate the association between intestinal inflammation and the gut microbiota remain unknown.…”
Section: Introductionmentioning
confidence: 99%